The Study on the Droop Effect in the InGaN/AlGaInN MQWs With Lattice-Matched AlGaN/InGaN Superlattices Barrier by Highly Excited Photoluminescence Measurement - Fulong Jiang; Yaying Liu; Menghan Liu; Ningze Zhuo; Peng Gao; Huajie Fang; Peng Chen; Bin Liu; Xiangqian Xiu; Zili Xie; Ping Han; Yi Shi; et al. (IEEE Photonics Journal)
We have fabricated the InGaN/AlGaInN multiple quantum wells with lattice-matched AlGaN/InGaN superlattices barriers (SL-MQWs). The lattice-matched superlattices promote the formation of the high-quality MQWs and eliminate the large polarization electric field. Highly excited photoluminescence measurement is performed by Ti-sapphire pulse laser with the maximal carrier density of 1020 cm−3. Under such high carrier density, the conventional InGaN/GaN MQWs (C-MQWs) have an additional nonradiative loss of carriers and suffer from the efficiency droop effect, while slight droop behavior is observed in the SL-MQWs sample. The results show that the substitution of AlGaN/InGaN superlattices as quantum barriers can effectively suppress the droop behavior at highly excited condition.